Tari Piriang Lenggang Manatiang di Sanggar Anjuang Siriah Kota Padang: Tinjauan Koreografi - Leri Yano Wardana; Nerosti Nerosti (SENDRATASIK UNP, 2023)
his research aims to describe and analyze the choreography of the Piriang Lenggang Manatiang Dance at the Anjuang Siriah Studio, Padang City. This type of research is qualitative research using descriptive analysis methods. The instrument for this research is the researcher himself and is assisted by supporting instruments in the form of writing instruments, books, recording equipment and audio-visual equipment. Data collection techniques were carried out using literature study, observation, interviews and documentation. The steps for analyzing data are data collection, data reduction, data presentation and conclusion. The results of the research show that the choreography process for the Piriang Lenggang Manatiang Dance starts from determining the idea/theme, then exploration, improvisation and composition. The choreography process produces the following form aspects: movement, space design, time design, energy design, top design, dramatic design, floor design, group composition, equipment and music. The movements of the Piriang Lenggang Manatiang Dance are the saayun steps, buai ayun movements, lenggang mantiang movements, manyabiak movements, rampak movements, saayun saangkat movements, Baginjai movements, ayun ma ayun movements, lenggang sway movements. The spatial aspect in the Piriang Lenggang Manatiang Dance uses straight, oblique and curved lines. The group compositions performed by dancers include unison (union), alternating, broken, alternating (canon), and balanced (balance). The Piriang Lenggang Manatiang Dance Costume is a garment that was developed and created by the Baju Kurong. The musical instruments used are Gandang, Bansi, Sarunai, Canang and Talempong Pacik. Meanwhile, the property used is piriang tujuah.